261 Association of T-cell–inflamed gene expression profile and PD-L1 status with efficacy of pembrolizumab in patients with esophageal cancer from KEYNOTE-180. (9th November 2020) - Shah, Manish; Kojima, Takashi; Hochhauser, Daniel; Enzinger, Peter; Raimbourg, Judith; Hollebecque, Antoine; Lordick, Florian; Kim, Sung-Bae; Tajika, Masahiro; Kim, Heung Tae; Craig Lockhart, A; Arkenau, Hendrick-Tobias; et al.
Abstract : Background: Key biomarkers under investigation for the ability to predict response to monotherapy PD-1 inhibitors such as pembrolizumab include PD-L1, TMB, MSI, and T-cell–inflamed gene expression profile (GEP). The KEYNOTE-180 trial (NCT02559687 ) was a single-arm phase 2 study of pembrolizumab as third-line or greater therapy in advanced/metastatic esophageal/gastroesophageal junction adenocarcinoma or squamous cell carcinoma (SCC). ORR was 9.9% and median DOR was NR at the primary analysis. We investigated the relationship in KEYNOTE-180 between response to pembrolizumab and T-cell–inflamed GEP or PD-L1 expression by histology. Methods: Patients received pembrolizumab 200 mg Q3W for ≤2 years until disease progression, toxicity, or withdrawal. The end points for this analysis were ORR, DOR, and PFS per RECIST v1.1 by central review and OS in the SCC and adenocarcinoma populations by GEP (non-low [≥–1.540] or low [<–1.540]; cutoff prespecified) and PD-L1 (CPS ≥10 or <10). Tumor GEP was determined using the NanoString nCounter Analysis System. PD-L1 expression was characterized using PD-L1 IHC 22C3 pharmDx. Data cutoff date was July 30, 2018. Results: Of 121 total patients, 118 had an evaluable GEP score and 121 had an evaluable PD-L1 CPS. Fifty-one patients (42.1%) had GEP non-low tumors, 58 (48.0%) had CPS ≥10 tumors, and 31 (25.6%) had GEP non-low /CPS ≥10 tumors; 63 patients (52.1%) had SCC and 58 (47.9%) had adenocarcinoma. ORR was 15.4% with GEP non-low and 13.5% with GEP low among patients with SCC and 12% and 0% among patients with adenocarcinoma, respectively (table 1). ORR was 20% with CPS ≥10 and 7.1% with CPS <10 among patients with SCC and 4.3% and 5.7%, respectively, among patients with adenocarcinoma (table 2). Median OS was slightly higher among patients with SCC in the GEP non-low subgroup and the CPS ≥10 subgroup versus GEP low and CPS <10 subgroups, respectively (tables 1, 2); this trend was reversed among patients with adenocarcinoma (tables 1, 2). Median PFS ranged from 1.9 to 2.1 across histology/biomarker subgroups. Median DOR was NR regardless of GEP or CPS status (tables 1, 2). Conclusions: In KEYNOTE-180, data in a small number of patients suggested that measures of inflammation, like PD-L1 and GEP, may enrich for responses to pembrolizumab. In SCC, some trends toward enrichment were observed for both biomarkers, although the trend was stronger for PD-L1 CPS ≥10. In adenocarcinoma, a trend was observed for GEP but not for PD-L1; the small number of responders is limiting, and further studies are needed to understand molecular correlates in adenocarcinoma. Acknowledgements: Medical writing and/or editorial assistance was provided by Tim Peoples, MA, ELS, and Holly C. Cappelli, PhD, CMPP, of the ApotheCom pembrolizumab team (Yardley, PA, USA). This assistance was funded by Merck Sharp & Dohme Corp, a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Trial Registration: ClinicalTrials. gov, NCT02559687 Ethics Approval: The study and the protocol were approved by the institutional review board or ethics committee at each site. Consent: All patients provided written informed consent to participate in the clinical trial.